The persisting influence of organized sports participation on mental health and wellness: a longitudinal repeated measures study of adolescent female athletes - Meyers, Rachel; Brna, Madison L.; Hogg-Cornejo, Veronica; Donahue, Catherine; Sweeney, Emily A.; Armento, Aubrey; Howell, David R. (Frontiers in Sports and Active Living, 2025)
PurposeWe examined if female adolescent athletes demonstrated changes on mental health measures 6-months after the end of a sport season compared to an immediate post-season assessment, and whether those who were actively playing sports 6-months after the end of the season reported different mental health ratings compared to athletes who were not.MethodsParticipants underwent three assessments: a pre-season, immediate post-season, and final 6-month post-season assessment on measures of anxiety ratings, depressive symptoms, grit, peer relationships, fatigue, and body appreciation.ResultsParticipants reported significantly higher anxiety ratings at 6 months post-season compared to immediately post-season (6.6 ± 4.2 vs. 7.7 ± 4.5; p = 0.02), but no significant differences across time for other outcome measures. Those who were actively participating in sports at the 6-month follow-up reported significantly higher body appreciation ratings than those who were not (41.7 ± 5.9 vs. 37.1 ± 7.6; p = 0.01).DiscussionOur findings indicate active sports participation is associated with higher body appreciation among female athletes.